NATURAL HISTORIES. EXTRAORDINARY BIRDS : Rare Book Selections from the American Museum of Natural History Library - Sweet, Paul; Capainolo, Peter, 1959-; Rhodes, Barbara J.; American Museum of Natural History. Library; American Museum of Natural History (New York : Sterling Signature, 2013)
The Beauty of Ornithology Revealed! Among the vast book holdings of the American Museum of Natural History Library are illustrated editions considered so valuable and rare, they are largely unseen by the public - until this series. Included in this elegant box set are : Extraordinary Birds, a monograph containing a history of ornithology, followed by essays about forty books that not only define the discipline but also feature masterworks of a variety of birds and fourty ready to frame prints, picture of reproduced artwork featured in each essay.
Foreword / by Ellen V. Futter Preface / by Tom Baione Introduction / by Paul Sweet Part 1. The history of ornithology / by Peter Capainolo Part 2. Essays & plates / by Paul Sweet ; The woodcut process / by Barbara Rhodes ; The engraving and etching processes / by Barbara Rhodes ; The lithographic process / by Barbara Rhodes.
At head of title: American Museum of Natural History.
Includes bibliographical references (page 131) and index.
Keywords: American Museum of Natural History -- Library -- Catalogs; Ornithological illustration -- Bibliography -- Catalogs; Birds -- Pictorial works -- Bibliography -- Catalogs; Birds in art -- Bibliography -- Catalogs; Ornithologists -- Biography; Animal painters -- Biography; Ornithology -- History; Ornithological illustration -- Technique; Birds -- Research; Rare books -- Bibliography -- Catalogs